Typology and inequality between island clusters and development areas in Maluku Province - Husen Bahasoan; Dedi Budiman Hakim; Rita Nurmalina; Eka Intan K Putri (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
This study aims to analyze patterns of economic growth and island cluster inequality in Maluku Province during the period 2010-2016. The data in this study are secondary data using quantitative descriptive methods and analytical typology analysis tools and theil index. The results showed that the VIII-IX island cluster which was classified as advanced and fast growing but had a very high inequality compared to other island cluster groups was Tual City, Southeast Maluku Regency and Aru Islands Regency. The division of the Maluku region in the Klassen typology is based on the center of growth with the hinterland area. Southern Maluku as a development area is classified as developed and fast-growing where Tual City is a center of growth but has a very high inequality compared to Maluku in the northern region.